Maternal and Perinatal Outcome of Threatened Abortion with Subchorionic Hemorrhage in First and Second Trimester - Kayastha, Bhagirathi; Shrestha, Abha (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Threatened abortion with subchorionic hemorrhage (SCH) is a common phenomenon during first and second trimester of pregnancy. Most pregnancies may continue to term and may be associated with poor maternal and fetal outcomes. The objective of this study was to assess the maternal and perinatal outcomes of threatened abortion with SCH in first and second trimester. Methods: This prospective study was conducted in Dhulikhel Hospital from August 2017 to July 2018. Total 150 cases were included in the study who had ultrasonography done to find out the size of SCH. They were followed up until spontaneous abortion or up to delivery of fetus. The outcomes were documented in terms of abortion, antepartum hemorrhage (APH), term or preterm vaginal delivery, cesarean section, intrauterine growth restriction (IUGR), low birth weight (LBW) and neonatal intensive care unit (NICU) admission. Results: The mean age was 25.39± 5.60 years and 59.33% were primigravida. 82.66% had SCH of size <4cm2 and rest had SCH of size ≥4cm2. 9.33% had spontaneous abortion. Among those whose pregnancy continued, 11.75% had preterm delivery, 14.70% had APH, 18.38% had IUGR, 11.76% had LBW and 13.97% had NICU admission. Conclusions: The size of SCH influences the pregnancy outcomes. Spontaneous abortion was seen more with SCH of size ≥4cm2 whereas continuation of pregnancy was seen more with SCH of size <4cm2. The associations of SCH of size ≥4cm2 with APH and IUGR were found to be significant whereas those with NICU admission and LBW were found to be insignificant.